Quality evaluation of innovative buttermilk biscuits produced from orange-flesh sweet potato flour infused with coconut - Ramsaran, Ronnie; de Gannes, Vidya; Eudoxie, Gaius (Frontiers in Food Science and Technology, 2024)
This study was undertaken to evaluate a value-added innovative buttermilk biscuit made from orange flesh sweet potato (OFSP) flour, infused with coconut. It underscores the importance of food utilisation through alternatives to wheat flour contributing to food and nutrition security amidst evolving global challenges. The objectives were: to investigate the effect of different levels of OFSP flour with and without shredded coconut on the physical, microbiological, nutritional and sensory properties of buttermilk biscuits. Methods: OFSP flour was produced and combined with wheat flour at different ratios and infused with desiccated shredded coconut to produce six formulations :100% wheat flour + 5% coconut (control 1), 100% wheat flour (control 2), 70% wheat flour + 30% OFSP flour + 5% coconut, 70% wheat flour + 30% OFSP flour, 50% wheat flour + 50% OFSP flour + 5 % coconut and 50% wheat flour + 50% OFSP flour. The study followed a randomised 3 x 2 factorial design where each treatment was replicated four times. Physical, nutritional, sensory, microbiological and shelf -life analyses were determined for each treatment. Results: The study's findings revealed that buttermilk biscuits formulated with 30% OFSP flour received the highest (p <0.05) sensory evaluation scores while the 100% wheat flour formulations received the lowest scores. Buttermilk biscuits contained protein, fat, fibre, moisture and ash. The colour L* of the OFSP flour treatments were significantly lower than the 100% wheat flour treatments. There were no significant changes in spread-ratio, diameter and thickness of the buttermilk biscuits during storage. Furthermore, the microbiological quality was maintained. The OFSP flour with and without desiccated coconut produced acceptable buttermilk biscuits with less reliant on wheat flour. It is noteworthy that the protein content of the OFSP flour buttermilk biscuits was at an acceptable level. Food safety was maintained throughout storage which is crucial in the elimination of food borne diseases. The use of different baking parameters can be used for future studies to assess the effect of temperature on the quality of buttermilk biscuits.